Are Purchase Intention Affected by Visual Social Media Marketing, Co-Branding, and Consumer Brand Engagement? - Waldi; Setiawan, Harry; Listiana, Erna; Barkah; Fitriana, Ana (Ilomata International Journal of Management, 2025)
Indonesia's footwear industry has experienced notable growth, particularly in the SME sector, creating opportunities for local brands like Aerostreet. This study examines the impact of visual social media marketing and co-branding on purchase intention, with consumer brand engagement as a mediating factor. The research used purposive sampling to select 227 respondents familiar with the Aerostreet brand, collecting data through a structured questionnaire. The investigation used Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the suggested hypotheses. The findings show that visual social media marketing positively and significantly impacts purchase intention. And enhances consumer brand engagement. Co-branding contributes positively to brand engagement, although it does not directly impact purchase intention. Nonetheless, brand engagement significantly influences purchase intention, serving as a mediator both between co-branding and purchase intention, and between social media visual marketing and purchase intention.